Using transcendental phenomenology in sequential mixed-methods approach for the development of a research anxiety scale for Filipino high school teachers - Ibañez, Mark Daniel M.
This study utilized transcendental phenomenology in exploratory sequential mixed-methods approach to develop the first 4-point Likert scale in the Philippines to quantify the research anxiety (RA) levels of Filipino high school teachers. Thematic analysis of in-depth interview responses resulted in themes about the experiences of teachers in studying and conducting research, which include enjoyment in research, understanding the value of research, difficulty in research, and the need for guidance, support, and constructive feedback. Themes related to experiences when working on research-related tasks include challenges in teaching research, feeling of untrustworthiness in addressing students’ research queries, humility to collaborate with experts, need for professional training, and learning from past experiences for better teaching and pedagogy. Themes on how teachers came to understand that they were experiencing RA include physical and physiological symptoms, cognitive and affective symptoms, and coping with RA. The constructed items were subjected to validity and reliability tests and factor analysis, adhering to the rigors of instrument development. The integration of the qualitative and quantitative results was presented through a joint display. The 62-item Research Anxiety Scale for Filipino Teachers (RAS-FiT) comprised factors including anxiety in teaching research, anxiety due to difficulty in research, negative attitudes toward research, anxiety in research requirements and activities, research self-efficacy, and anxiety due to lack of research knowledge and skills. The RAS-FiT manual was prepared for scoring and score interpretation along the RA continuum. The scale results may be utilized to design intervention programs to alleviate RA toward greater research productivity among 21st century teachers.